DISRUPTING SELF-SABOTAGE THROUGH SELF-COMPASSION: AN INTEGRATIVE COUNSELING FRAMEWORK FOR MALADAPTIVE BEHAVIORAL CYCLES - Saidi, Liley Afzani; Rahaman, Nur Haffiza; Wan Yusof, Wan Sue Emi Yusnita; Ramlee, Siti Nurhafizah Saleeza; Abdullah, Rayyan Cheong Tiang Ming (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Self-sabotage represents a recurring and self-defeating behavioral cycle that impairs personal, emotional, and goal-oriented functioning. Despite extensive reliance on cognitive-behavioral techniques to address its symptoms, these approaches often fail to resolve the deeper emotional roots—particularly shame, self-criticism, and emotional dysregulation. This conceptual paper introduces a theoretically integrated counseling framework in which self-compassion functions as a core mechanism for disrupting maladaptive behavioral cycles. Synthesizing elements from Compassion-Focused Therapy (CFT), Cognitive Behavioral Theory (CBT), and Self-Determination Theory (SDT), the framework posits that self-sabotaging behaviors are maintained through the dynamic interaction of negative self-appraisal, emotional threat responses, and thwarted psychological needs. In response, self-compassion defined through mindfulness, self-kindness, and the recognition of shared human fallibility offers a corrective emotional and motivational process. This approach enables clients to regulate internal shame, challenge harsh inner narratives, and re-engage with personally meaningful values and goals. Specific interventions such as compassionate reframing, values clarification, and mindfulness training are positioned as therapeutic tools to promote emotional safety, psychological flexibility, and long-term behavioral change. The discussion critically examines the strengths of this model, including its compatibility with trauma-informed practice and its capacity to bridge cognitive and affective interventions. Potential challenges such as client resistance to self-compassion and cultural misinterpretations are also addressed. Ultimately, this paper highlights the transformative role of self-compassion in counselling and calls for its empirical validation in clinical settings where self-sabotage is prevalent.